PENGARUH PAJAK DAERAH, RETRIBUSI DAERAH, LAIN-LAIN PAD YANG SAH TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN/KOTA DI PROVINSI SULAWESI TENGGARA - Novita Wulandari; Buyung Sarita; Wahyuniati Hamid; Zaluddin Zaluddin (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2022)
The This study aims to examine and analyze the effect of Regional Taxes, Regional Retribution, and Other legitimate local revenue on Regency/City Original Revenues in Southeast Sulawesi Province for the 2015-2019 period. The population in this study is a report on the realization of the revenue budget in the form of Regional Taxes, Regional Retribution, and Other legitimate local revenue and Regency/City local-owned source revenue in Southeast Sulawesi Province. The data used in this study is secondary data that uses a time series for the 2015-2019 period, totaling 85 observational data. Hypothesis testing using multiple linear regression analysis, using SPSS (Statistical Product and Service Solutions).                  The results of the research analysis show that Regional Taxes have a positive effect on local-owned source revenue, Regional Retribution have a positive effect on local-owned source revenue, and Other legitimate local revenue also shows a positive influence on local-owned source revenue. Meanwhile, in the determination test, it is said that Regional Taxes, Regional Retributions, and Other Legitimate PAD contribute to local-owned source revenue by 97.9%, the remaining 2.1% is obtained from other factors not examined. So it can be concluded that Regional Taxes, Regional Levies, and Other legitimate local revenue are the main contributors to local-owned source revenue.